Can Video Enhance Confidence in Management of Vaginal Pessary: A randomized trial - Siwarut Buakhom; Teerayut Temtanakitpaisan; Chompilas Chongsomchai; Maleechat Sripipattanakul; Pranom Buppasiri (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To compare the confidence of women with pelvic organ prolapse (POP) in vaginal pessary management between those who had versus those who hadn't watched the teaching video. Materials and Methods: This randomized clinical trial was conducted at two urogynecological clinics in Khon Kaen, Thailand, from September 2017 to May 2018. Women with POP that require for vaginal pessary were included and were randomized into two groups: 1) treatment group received brochure and watched teaching video, and 2) control group received only educational brochure. Each participant's knowledge was tested before and after receiving construction from a trained nurse. A retest, which examined participants' knowledge retention, self-confidence, and satisfaction in pessary use, was conducted at a two-week follow-up visit. Results: A total of 50 subjects were enrolled: 25 in each video and non-video group. There was no statistically significant difference in median confidence scores between video (median; range = 10; 7-10) and non-video (median; range = 10; 5-10) groups, p = 0.917. There was statistically significant difference in mean pretest and posttest scores in both video and non-video group (3.72 [95%CI 2.98-4.46], p < 0.001 and 3.84 [95%CI 3.10-4.58], p < 0.001, respectively) but no significant difference between two groups (0.12 [-0.60-0.84], p > 0.999). However, the median time required to practice using pessary was significantly shorter in the video group (10 minutes [5, 30] and 15 minutes [7, 20], p = 0.001). Conclusion: Additional teaching video didn't affect confidence in vaginal pessary management. However, this tool enhanced patients' learning.